HUBUNGAN IKLIM KESELAMATAN KERJA TERHADAP PERILAKU TIDAK AMAN PEKERJA PROYEK RENOVASI PT X DI NUSA DUA - Revita Dea Sari; I Nyoman Sutarsa (ARCHIVE OF COMMUNITY HEALTH, 2023)
The construction sector is a contributor to increase number of accidents and occupational illness. Unsafe behavior in the workplace is directly related to work accidents. One of the factors that can influence unsafe behavior is the worker's perception of the safety climate. This study aims to analyze the correlation between perceptions of safety climate and unsafe behavior of construction workers on the renovation project of PT X in Nusa Dua. Quantitative research was conducted using an analytical cross-sectional approach. Respondents in the study are 200 people who were selected by the block sampling method. This study found that the proportion of respondents behaved unsafely was 60.5%. Unsafe behavior was found to be significantly related to safety empowerment management (p=0.042), worker commitment (p=0.012), priority and risk tolerance (p=0.007), and communication and trust in implementation (p=0.040). In multivariate analysis, respondents who have good perceptions of communication and trust in implementation had a 2.63 times chance of reducing unsafe behavior compared to who had sufficient perceptions. As an effort to increase safety behavior, workers are expected to be more concerned with the risk of hazards in the workplace by complying with occupational safety health programs. Keywords: the construction workers, unsafe behavior, perception of safety climate